IMPLEMENTATION OF SUPPORTIVE SUPERVISION TO OVERCOME TEACHER ANXIETY AT MTsN 2 SIAK - Ahmad Hilal; Syafarudin Syafarudin; Tuti Andriani (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to qualitatively analyze the implementation of supportive supervision by the school principal as an effort to overcome teacher anxiety at Madrasah Tsanawiyah Negeri 2 Siak. Specifically, this research aims to determine the factors causing teacher anxiety, identify the steps of supportive supervision implementation carried out by the school principal; and analyze the supporting and inhibiting factors of the supportive supervision implementation. This type of research is field research with a qualitative approach that uses interviews, observation, and documentation as data collection techniques. The research was conducted at Madrasah Tsanawiyah Negeri 2 Siak. The research results show that the main factors causing teacher anxiety are immaturity in lesson preparation, lack of deep and comprehensive knowledge, inability to teach certain subjects, problems faced by students related to school, the school building environment, and the principal's supervision. The implementation of supportive supervision is carried out through structured and collaborative steps, including: Planning, execution, feedback, evaluation and analysis of supervision results, follow-up plan, and supervision implementation report. Supporting factors for the implementation of supervision include emotional support, instrumental support, appreciation, information, social integration, and spiritual support. Meanwhile, the inhibiting factors are lack of a scientific spirit among teachers, weak creativity, and lack of facilities.